Evidence of short-range screening in shock-compressed aluminum plasma - Garcia Saiz, E; Gregori, G; Khattak, F; Kohanoff, J; Sahoo, S; Naz, G; Bandyopadhyay, S; Notley, M; Weber, R; Riley, D (2008)
We have investigated the angular variation in elastic x-ray scattering from a dense, laser-shock-compressed aluminum foil. A comparison of the experiment with simulations using an embedded atom potential in a molecular dynamics simulation shows a significantly better agreement than simulations based on an unscreened one-component plasma model. These data illustrate, experimentally, the importance of screening for the dense plasma static structure factor. © 2008 The American Physical Society.